Dynamic Games in Economics - Haunschmied, Josef.; Haunschmied, Josef.; Veliov, Vladimir M.; Veliov, Vladimir M.; Wrzaczek, Stefan.; Wrzaczek, Stefan. (Dynamic Modeling and Econometrics in Economics and Finance,, 2014)
Dynamic game theory serves the purpose of including strategic interaction in decision making and is therefore often applied to economic problems. This book presents the state-of-the-art and directions for future research in dynamic game theory related to economics. It was initiated by contributors to the 12th Viennese Workshop on Optimal Control, Dynamic Games and Nonlinear Dynamics and combines a selection of papers from the workshop with invited papers of high quality.